Endoscopy in Pediatric Inflammatory Bowel Disease: A Position Paper on Behalf of the Porto IBD Group of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition. Issue 3 (September 2018) - Oliva, Salvatore; Thomson, Mike; de Ridder, Lissy; Martín-de-Carpi, Javier; Van Biervliet, Stephanie; Braegger, Christian; Dias, Jorge Amil; Kolacek, Sanja; Miele, Erasmo; Buderus, Stephan; Bronsky, Jiri; Winter, Harland; et al.
Abstract : ABSTRACT: Endoscopy is a central tool for the evaluation and management of inflammatory bowel disease (IBD). In the last few decades, gastrointestinal (GI) endoscopy has undergone significant technological developments including availability of pediatric-size equipment, enabling comprehensive investigation of the GI tract in children. Simultaneously, professional organization of GI experts have developed guidelines and training programs in pediatric GI endoscopy. This prompted the Porto Group on Pediatric IBD of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition to develop updated guidelines on the role of GI endoscopy in pediatric IBD, specifically taking into considerations of recent advances in the diagnosis, disease stratification, and novel therapeutic targets in these patients.